Use of orthospin technology in the correction of complex limb deformities - Adam D Geffner; Taylor J Reif; Austin T Fragomen; S Robert Rozbruch (Annals of Robotics and Automation - Peertechz Publications, 2021)
Circular external fixators using hexapod struts are a valuable tool in the treatment of complex, multiplanar limb deformities. The benefits of external fixation technology are well documented and include excellent biomechanical fixation allowing weight bearing and range of motion of joints during treatment, as well as superb versatility to manage a host of challenging clinical pathologies. Despite these advantages, proper treatment with a hexapod external fixation device depends on the patient's ability to manually adjust the six struts according to a demanding treatment plan. Without strict adherence to the treatment plan, prolonged treatment, worsening deformity, or even the need for further surgery become possible. Orthospin's Autostrut technology provides a solution to the drawbacks of external fixation treatment by automating the strut-adjustment process. A control box automatically turns motorized struts according to the physician's treatment plan and sends real-time updates to the physician's phone or computer. This allows him or her to closely monitor the treatment process and make necessary adjustments as needed. Orthospin technology is FDA approved and given its success in early applications is ready for more widespread use.